Comparison among wheat seeds produced in Mexico and in Brazil - Linhares, A. G.; Nedel, J. L. (Pesquisa Agropecuaria Brasileira, 2014)
Wheat seeds produced in Mexico (Ciudad Obregon-Sonora) and in Brazil (Passo Fundo, RS, Brasília, DF) were compared in a field trial to assess the effect of origin on the stand, dry weight of above-ground part of plants, number of spikes, and yield. The experiment was conducted at the Centro Nacional de Pesquisa de Trigo - CNPT/EMBRAPA, in 1981 and 1982. The experiment was conducted in a completely randoming block design, with 15 treatments in split-plot arrangement (5 cultivars x 3 sources of origin, and four replications. Seeds were dressed with fungicide and the plants sprayed with fungicides and insecticide to control foliar diseases and pests. In spite of some difficulties to overcome dormancy of seeds produced in Brasília and of extremely adverse environmental conditions in 1982, it was considered that the parameters were correctly assessed. Coefficients of variation were low and yield levels considered satisfactory. The results obtained in the two years under study, from the characteristics assessed, showed no consistent superiority for the seeds produced in Mexico as compared to the ones produced in Brazil.